The Influence of Green Accounting and Capital Structure on Financial Performance with Environmental Performance (Proper Index) as a Moderation Variable - Anisah, Nur Wafa; Hamzani, Umiaty; Yunita, Khristina; Dosinta, Nina Febriana; Damayanti, Fera (STMIK Widya Cipta Dharma, 2024)
This research aims to examine the relationship between green accounting and capital structure on financial performance, moderated by environmental performance within appropriate indices. The research population includes energy and mining companies listed on the IDX during 2021–2023, with the sample selected using purposive sampling techniques. The sample comprises 30 companies and 90 data points. Secondary data were utilized, drawn from annual reports and sustainability reports. The analytical tool employed in this research is EViews 13, using multiple linear regression and moderated regression analysis techniques. The results reveal that green accounting has a significant effect on financial performance, while environmental performance does not moderate the relationship between green accounting and financial performance. Capital structure does not have a significant effect on financial performance, but environmental performance moderates the relationship between capital structure and financial performance. This research contributes to the environmental accounting and financial strategy literature by emphasizing the importance of green accounting and environmental performance management in enhancing corporate value. Furthermore, the findings provide valuable insights for companies in developing sustainability strategies and effectively managing their capital structure.